Supply Chain Risk Management System for The Wooden Educational Toy Manufacturing Industry in Bekasi, West Java - Veronica, Widya Ruth; Azmi, Nora; Kemalasari, Debbie (Jurnal Ilmiah Teknik Industri, 2025)
The wooden educational toy manufacturing industry plays an important role in supporting children's cognitive and motor development, while presenting its own challenges in operational and supply chain management. The complexity of managing raw material supply, meeting the requirements of product safety and delivery standards, and adjusting to fluctuations in market demand may pose interrelated risks. This problem will have an impact on the company's operational effectiveness. This research aims to identify the causes of the main risks, map the relationships between risks, and determine priority mitigation strategies. The methods used are House of Risk (HOR) for risk identification and mitigation strategies based on the Aggregate Risk Potential (ARP) value, and Analytical Hierarchy Process (AHP) to prioritize mitigation strategies based on Safety, Cost, Time, and Effectiveness criteria. Activity identification was conducted through the Supply Chain Operations Reference (SCOR) approach and visualized using a Network Diagram Model with K-Means Clustering. This research identified 12 main supply chain activities to obtain the main cause of 44 Risk Events based on 24 Risk Agents. The results showed that 8 mitigation strategies were designed with the highest priority being regular coordination between departement against the cause of lack of effective communication. Through this research, it was found that the implementation of the selected mitigation strategies can significantly reduce operational risk and improve supply chain efficiency